SOCIAL MEDIA - Sobirova Muxtasaroy (Uzbekistan, Andijan) Ahmedov Azimjon Ilhomovich (Uzbekistan, Andijan) (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2023)
The majority of teens have positive online experiences, but some are caught in an online feedback loop of meanness and negative experiences. The majority of social media-using teens say their experience is that their peers are mostly kind to one another on social network sites, but their views are less positive when compared with similar assessments from online adults.